Poziom i jakość życia ludności oraz źródła i mierniki ich określania - Piasny, Janusz (Wydział Prawa i Administracji UAM, 1993)
The author points to the complexity of determining the standard and quality of living in theory and practice. He stresses the need to develop various sources of information and sociostatistical tools of their analysis within a so-called Integrated System of Household Research. In t h e article the author: — defines the standard of living and discusses synthetic and analytic measures of its determining; — defines the concept of the "quality of living" and subjective and objective measures allowing to assess its changes; — points to the advantages and disadvantages of household budget research, agricultural accounting of farms and other forms of research as sources of information on different aspects of t h e standard and quality of living; and — makes a synthetic review and evaluation of the outcome of the research on the quality of living in the early 90s in Poland. Among the conclusions concerning the improvement of the system of analyzing t h e standard and quality of living mention should be made of: — the need to analyze the standard and quality of living in conjunction with the economic, demographic, sociological and psychological factors shaping the standard and quality of living; — the need to include into the research new socio-economic groups (self-employed families and so-called free professions); — the need to adjust the classification of revenues and expenses of t h e population to Western European standards; — the need to improve the methodology of estimating living expenses, and the methodology of calculating income and real pay; — the need to develop and improve the research not only on the standard of living, but also on the "quality of living", in order to fully employ these categories to solving various social policy problems.
Standard and quality of living